Aqua vitae – Notes on Geographies of Alcohol Production and Consumption in the Ottoman Balkans - Jelena Mrgić (University of Belgrade, 2017)
The paper addresses the beginning of brandy distillation in the Ottoman Balkan, the transfer of technology, commerce and taxation, as well as patterns of consumption. Those patterns include rules of alcohol production, distribution and use according to religion, class and gender, i.e. restrictions and their transgressions. Linguistic, documentary and narrative sources are deployed in building a multifaceted picture. Production of various spirits, foremost plum brandy in the Ottoman Balkans, and the usage of alcohol drinks could be viewed as an area where private and public, official and clandestine, permitted and forbidden mixed and coexisted, and influenced Ottoman political and religious system.